Conversational Gambits used by the English Education Program Students of Graduate Program of State University of Padang in Classroom Discussion - Ariani, Desti (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2018)
This research is a descriptive research which aims at describing conversational gambits used by the English Education Program students of Graduate Program of Padang State University in organizing their utterances and interaction in classroom discussion. Purposeful sampling was used to choose 5 classroom discussions and 13 students who actively gave verbal contribution through the using of conversational gambits. The instruments used in this research were observation, field note, and also interview. The finding showed that the type of conversational gambits frequently used by the students in classroom discussion was linking gambits. The gambits used were frequently functioned as communication control. The research also revealed that the students tended to utter certain conversational gambits; âokayâ and âI thinkâ more frequently than others which was caused mainly by their habit in using those gambits in their daily communication.